Core-Shell Magnetic Nanoparticles for Highly Sensitive Magnetoelastic Immunosensor - Raffaele Campanile; Emanuela Scardapane; Antonio Forente; Carmine Granata; Roberto Germano; Rocco Di Girolamo; Antonio Minopoli; Raffaele Velotta; Bartolomeo Della Ventura; Vincenzo Iannotti (Nanomaterials, 2020)
A magnetoelastic (ME) biosensor for wireless detection of analytes in liquid is described. The ME biosensor was tested against human IgG in the range 0–20 μg∙mL−1. The sensing elements, anti-human IgG produced in goat, were immobilized on the surface of the sensor by using a recently introduced photochemical immobilization technique (PIT), whereas a new amplification protocol exploiting gold coated magnetic nanoparticles (core-shell nanoparticles) is demonstrated to significantly enhance the sensitivity. The gold nanoflowers grown on the magnetic core allowed us to tether anti-human IgG to the nanoparticles to exploit the sandwich detection scheme. The experimental results show that the 6 mm × 1 mm × 30 μm ME biosensor with an amplification protocol that uses magnetic nanoparticles has a limit of detection (LOD) lower than 1 nM, works well in water, and has a rapid response time of few minutes. Therefore, the ME biosensor is very promising for real-time wireless detection of pathogens in liquids and for real life diagnostic purpose.